'I didn't feel like I was alone anymore': evaluating self‐organised employee coping practices conducted via Facebook. (November 2015) - Cohen, Nicola; Richards, James
Abstract : The long‐term fracturing of the labour movement has led to increased attention to employee coping practices under new management practices and labour processes. However, the literature caters little for the recent rise of employees taking to social networking sites (SNSs), such as Facebook, to find ways to cope with the pressures of contemporary employment. To explore the self‐organised coping qualities of SNSs, interviews were conducted with front line workers, employed by a large anti‐trade union US retailer, who contribute to a self‐organised Facebook group set up as a place for fellow employees to deal with collective employment‐related problems. The main findings suggest employee self‐organised Facebook groups represent an important development and extension to the coping practices available to individual and groups of employees. The main implication of the findings is that Facebook groups appear to strengthen and widen the options for employee resilience in an age of continuing trade union retreat.